Alquran dan Toleransi di Indonesia: Sebuah Analisa Surat al-Bāqarah: 148 - Muhammad Alan Zuhri (Qur'an and Hadith Academic Society, 2018)
This paper discusses tolerance based on Surah al-Bāqarah verse 148. By using the method of library study, the researcherdiscusses different views on tolerance from religious perspectives, especially based on Surah al-Bāqarah verse 148. This study finds information that this first has been used to emphasize two things: first, the importance of respecting diversity as an objective fact, secondly the importance of striving seriously in terms of goodness as an important element in a pluralistic society.